(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Elena N. Lyashenko (Rostov-on-Don, Russian Federation) Color naming is the subject of the representatives of different branches of knowledge – ethnographers, philologists, culture experts, psychologists, political scientists and many other professionals. The ability of color units to transmit values that go beyond the designation of color, is widely used in the literature, in everyday speech, in the advertising field. In recent years, interest has increased in linguistics to the study of color naming in advertising function. The present work is devoted to identifying ways of lexeme nomination «green» in the English-language advertising texts of civil engineering sphere. Most extra-linguistic factors are the cause of changes in the semantic structure of the word. The global environmental crisis, the issue of harmonization of man and nature contribute to the development of relations in this terminological adjective meaning of «environmentally friendly». In the studied texts the following methods of updating the value of «green» are presented: terminologization, varying forms, the creation of a pun. Inclusion in the text of comparatives and superlatives results in deliberate ambiguity statements: on the one hand, it is reported on the benefits of environmentally friendly products, on the other – the color component is updated. Ambiguity of the «green» advertising has a pragmatic focus, it is meant to attract the attention of potential consumers, create a positive image of the product, increase evaluative statements. Key words: color naming «green», ambiguity, terminological and common language values, comparative design, pragmatic installation of ad text, environmental protection.